Automated method of calculating the parameters of the complex hydroelectric power system operating in heating mode - Olishevskyi, I. H.; Titov, M. G. (НТУ ДП, 2024)
The use of heat pumps is one of the most energy-efficient ways of heating residential and industrial premises. Electricity consumption for the heat pump drive is usually lower than gas consumption in the boiler plant, both in energy equivalent (reduced to conventional fuel) and in monetary terms.